Financial derivatives modeling - Ekstrand, Christian; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book gives a comprehensive introduction to the modeling of financial derivatives, covering all major asset classes (equities, commodities, interest rates and foreign exchange) and stretching from Black and Scholes' lognormal modeling to current-day research on skew and smile models. The intended reader has a solid mathematical background and is a graduate/final-year undergraduate student specializing in Mathematical Finance, or works at a financial institution such as an investment bank or a hedge fund.
Derivatives Pricing Basics: Pricing by Replication -- Static Replication -- Dynamic Replication -- Derivatives Modeling in Practice -- Skew and Smile Techniques: Continuous Stochastic Processes -- Local Volatility Models -- Stochastic Volatility Models -- Lévy Models -- Exotic Derivatives: Path-Dependent Derivatives -- High-Dimensional Derivatives -- Asset Class Specific Modeling: - Equities -- Commodities -- Interest Rates -- Foreign Exchange -- Mathematical Preliminaries.
Electronic reproduction.
Keywords: Derivative securities -- Mathematical models; Derivative securities -- Prices -- Mathematical models; Electronic books